Turnover Intention among Private School Teachers in Madura: Empirical Evidence of the Mediating Role of Organizational Commitment - Alvin Arifin; Endang Suswati; Sugeng Mulyono; M. Jamal Abdul Nasir; Martaleni (PT FORMOSA CENDEKIA GLOBAL, 2026)
High turnover intention among private school teachers poses a serious challenge to educational continuity, particularly in regions with limited retention capacity such as Madura Island. This study examines the effects of resilience and life demands on turnover intention, with organizational commitment as a mediating variable. Using a quantitative explanatory approach, data were collected through a structured survey of 100 private school teachers selected via proportional random sampling across four regencies on Madura Island. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that organizational commitment significantly reduces turnover intention and fully mediates the effects of resilience and life demands. These results underscore the critical role of organizational commitment in shaping teachers’ retention decisions.